Tuberculous aortitis in an human immunodeficiency virus–positive Ivorian migrant: A case report. (December 2021) - Fama', Fausto; Sindoni, Alessandro; Donato, Rocco; Cascio, Antonio; Mondello, Placido; Gaeta, Roberto
We report an unusual case of a 35-year-old Ivorian migrant with an abdominal mass and medical history relevant for human immunodeficiency virus-2 positivity with a CD4/CD8 ratio of 0.63; Mantoux and lymphocyte stimulation tests (QuantiFERON) were positive. 3D-CT images revealed a voluminous non-homogeneous retroperitoneal mass in the right abdominal region presenting no significant contrast impregnation. Thoraco-abdominal aorta presented diffuse-altered morphology with multiple ectasias throughout its course and an aneurysm at the level of the subrenal tract. The patient underwent vascular surgery. Mycobacterium tuberculosis complex was detected by polymerase chain reaction performed on intraoperative tissue specimens. Postoperative course was uneventful. After surgery, 3D-CT images showed no signs of malfunction of the prosthesis. At last, at 6-month follow-up, the patient was well. Cross-sectional imaging techniques, such as contrasted-CT, are essential and allow for making diagnosis, assessing disease activity, and evaluating post-treatment condition. 3D reconstruction permits an appropriate patient care by means of an excellent visualization and staging of the disease process.